Prevalence and correlates of anemia among women in the reproductive age (15-49 years) in a rural area of Tamil Nadu: An exploratory study - A Jenit Osborn; G M Muhammad; S L Ravishankar; Anil C Mathew (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Anemia is a major public health problem among reproductive-aged women in India. Despite many programs implemented for decades to fight anemia, still the prevalence of anemia is high because its associated factors vary among different regions. This exploratory study was carried out to find the prevalence of anemia and factors influencing it among nonpregnant reproductive-aged women (15-49 years) in a rural area of Coimbatore. MATERIALS AND METHODS: The study was conducted in the field practice area of Rural Health Training Centre, PSG IMSR, Coimbatore, during March 2016 to August 2016. Participants were recruited by two-staged random sampling method and 426 participants were enrolled. A predesigned semi-structured questionnaire was used to collect the data pertaining to the factors influencing the prevalence of anemia, and their hemoglobin level was measured using a hemoglobin photometer. The data were analyzed using SPSS-24. (IBM Corporation, SPSS Inc., Chicago, IL, USA) Univariate analysis was done using Chi-square test and the strength of association was estimated by odds ratio. Those factors which were found to be significant by univariate analysis were further subjected to multivariate logistic regression analysis. P < 0.05 was considered statistically significant. RESULTS: The prevalence of anemia was estimated as 64.8% (95% confidence interval: 60%-69%). Significant predictors for anemia among the study participants were less frequent intake of green leafy vegetables (adjusted odds ratio [AOR] = 3.65, confidence interval [CI]: 2.17-6.12), low socioeconomic status (AOR = 3.36, CI: 1.93-5.84), illiteracy (AOR = 3.09, CI: 1.09-5.24), birth spacing <2 years (AOR = 2.49, CI: 1.19-5.25), excessive menstrual bleeding (AOR = 2.27, CI: 1.09-4.76), and inadequate knowledge regarding anemia (AOR = 2.03, CI: 1.19-3.44). CONCLUSION: Anemia is still prevalent in high magnitude in reproductive-aged women, and measures to prevent and control it are not optimum. Hence, its multifactorial determinants have to be addressed to alleviate its burden.